Pattern of Organization in Literal Reading - Hafidah, Agustina Sri; Hadi, Samsul; Narajati, Rayhan; Yanti, Sherina Fedila; Rizkyanto, Yuanda Khalif (Berpusi Publishing, 2024)
Language is the ability that humans have to communicate with other humans using signs, such as words and movement. Without language, information will not be conveyed easily and there will be many limitations that occur. One of the languages that is often used in the world is English. Therefore, English is very important for everyone to learn. In learning language, there are four major skills to complete the language. Those four skills are listening, speaking, reading, and writing. In this article, the writer wants to know about what is reading, to get to know what Patterns of Organization are, and to determine reading comprehension through Patterns of Organization . The author uses the literature review method, whereas with this method, the author reviews various sources from existing literature. In order for this article will be useful for a wide audience in general and also for academics, including students, teachers, university students, and lecturers in particular.